Hand painted rustic cards - Watkins, ruth (Tunbridge, England Search press, 2008)
you can learn how to creat beautiful hand painted rustic cards using just acrylic paints and a waterproof pen, the content suppurted by simple projects at the start and Templates are provided for all of the designs
Keywords: Handicraft